The Safety of the Thenar Portal: An Anatomical Study of the Thumb Carpometacarpal Arthroscopy - Pan, Yong-wei; Hung, Leung-kim (Journal of Wrist Surgery, 2017)
Purpose To define the localization of the distal course of the motor branches of median nerve (MBMN) and its arborization and its quantitative relationships to the thenar portal of the carpometacarpal (CMC) joint in the hope of evaluating the safety of this portal.Method In 16 embalmed cadaveric upper extremities, the localization of the course of the MBMN and its arborization were defined. In 14 fresh-frozen cadaver upper extremities, the CMC arthroscopic portals, 1-U, 1-R, and a thenar portal, were established, after which the limbs were dissected. Measurements were taken from the portals to the superficial radial nerve, radial artery, and the MBMN.Results The distal course of the MBMN and its terminal branches were all located in the proximal third of the thenar muscles, where the thenar portal was introduced. The mean distances between vital structures and each traditional portal (1-R or 1-U) were consistent with the previously published studies. Both the superficial and the profound branches of MBMN were very close to the thenar portal, and the distance between these two main terminal branches and the thenar portal was 1.2 mm (range: 0–6.2; standard deviation [SD] = 2) and 2.2 mm (range: 0–7; SD = 2.1), respectively. Five (35.7%) of the 14 fresh-frozen specimens indicated the superficial branch lay directly over the portal. One hand (7.1%) had the profound branch crossed over the thenar portal. Four hands (28.5%) indicated both the superficial and profound branches directly overlay the thenar portal. The superficial palmar branch of the radial artery was found in six hands, and in four of them, it crossed over the thenar portal.Conclusion The distal course of the MBMN and its terminal branches were all located in the proximal third of the thenar muscles, where the thenar portal was introduced.Clinical Relevance The thenar portal could improve the view of the CMC joint of the thumb and provide better performance of procedures in this joint. We should bear in mind that the arborization of the MBMN was mostly located in the proximal third of the thenar muscle, and any operation in this area should be performed with great caution.
Keywords: arthroscopy; carpometacarpal; portal